2022
DOI: 10.3390/en16010031
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Return-on-Equity (ROE) of Biogas Plants Operating in Poland

Abstract: Poland has a large potential for biogas production from agricultural sources and food waste. This potential is still poorly used. There are many reasons for this state of affairs. We can indicate both the policy of the state towards renewable energy sources (RES) with a small amount of energy from biogas contracted at auctions, investment risk, and especially low return on investment in the absence of investment support. An important reason is also the limited state budget. The purpose of this work was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The reasons for the low coverage levels are the high amount of electricity used, the limited variety of animal waste included in biogas production and the number of animals. Ertop et al [53] stated that the total installed capacity of 106 biogas plants in Turkey is 675.42 MW, while Kusz et al [70] reported that the total installed capacity of 128 biogas plants in Poland is 125.323 MW. Considering the electricity consumption in Table 10, it can be found that the capacity of biogas production facilities in both countries should be increased.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for the low coverage levels are the high amount of electricity used, the limited variety of animal waste included in biogas production and the number of animals. Ertop et al [53] stated that the total installed capacity of 106 biogas plants in Turkey is 675.42 MW, while Kusz et al [70] reported that the total installed capacity of 128 biogas plants in Poland is 125.323 MW. Considering the electricity consumption in Table 10, it can be found that the capacity of biogas production facilities in both countries should be increased.…”
Section: Resultsmentioning
confidence: 99%
“…The main points of establishing layered indicators are process, planning and systematic, in order to increase the turnover of the enterprise, improve the utilization of assets and control a reasonable financial structure at the guideline level set two key indicators, which are the profitability of assets, asset turnover [21]. Satisfaction of the company's departments, increasing the share of the enterprise's business in the market, and the increase in market share are the main indicators of performance assessment at the management level.…”
Section: Design Of Management Evaluation Indicatorsmentioning
confidence: 99%
“…Return on Equity (ROE) reflects the efficiency of own money. The formula for calculating Return on Equity (ROE) is EAT divided by Equity (Zulkarnain et al, 2022;Kusz et al, 2023;Saputra 2022). Measure the company's ability to generate net profit from sales made.…”
Section: Introductionmentioning
confidence: 99%